Nutrient identity modifies the destabilising effects of eutrophication in grasslands. (27th December 2021) - Carroll, Oliver; Batzer, Evan; Bharath, Siddharth; Borer, Elizabeth T.; Campana, Sofía; Esch, Ellen; Hautier, Yann; Ohlert, Timothy; Seabloom, Eric W.; Adler, Peter B.; Bakker, Jonathan D.; Biederman, Lori; et al.
Abstract: Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability. Abstract : Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, using data from 34 grasslands over 7 years, we show prevalent destabilisation with fertilisation was driven by single‐nutrient effects on the temporal standard deviation of biomass production but was not influenced by synergistic interactions among multiple nutrients. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony.